2022
DOI: 10.2174/1574886317666220207120649
|View full text |Cite
|
Sign up to set email alerts
|

Active Symptom-Based Surveillance of Adverse Events Following Immunization Among Individuals Vaccinated with ChAdOx1 nCoV-19 Coronavirus Vaccine in a Tertiary Hospital of Kerala

Abstract: Background: The reports on adverse experiences following vaccination are scanty from India. It is important to know the real-world post-vaccination experience outside of clinical trial conditions Objectives: To estimate the incidence of adverse events following immunization with ChAdOx1 nCoV-19 coronavirus vaccine and to identify the predictors for development of vaccine adverse events Materials and Methods: A prospective observational study was conducted among health care workers who received the ChAdOx1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Among those participants experiencing any AEFI in our study, majority (119, 99.0 %) experienced only mild/minor grade AEFI with only 2(1.0 %) experiencing a severe AEFI requiring hospitalization but without any sequelae or long-term complication. Similar results were reports by other studies from various parts of India [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] and across the globe [29] , [30] , [31] , [32] , [33] . In the study by Kamal et al [22] , two serious AEFI (altered sensorium) were reported within 48 h after the 1st dose of COVISHIELD TM vaccine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among those participants experiencing any AEFI in our study, majority (119, 99.0 %) experienced only mild/minor grade AEFI with only 2(1.0 %) experiencing a severe AEFI requiring hospitalization but without any sequelae or long-term complication. Similar results were reports by other studies from various parts of India [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] and across the globe [29] , [30] , [31] , [32] , [33] . In the study by Kamal et al [22] , two serious AEFI (altered sensorium) were reported within 48 h after the 1st dose of COVISHIELD TM vaccine.…”
Section: Discussionsupporting
confidence: 90%
“…Studies by Kushwaha et al [17] from North India and Kujur et al [18] from Eastern India assessing AEFI with 1st dose of COVISHIELD and Parida et al [16] from Eastern India assessing AEFI with Covaxin reported similar figures of 30.4 %, 33.6 % and 29.8 % respectively. However, studies by Kaur U et al [19] , Kaur S et al [20] and Jha et al [21] from North India reported the incidence of AEFI as 40.0 %, 46.0 % and 73.9 % respectively with 1st dose of COVISHIELD TM whereas studies by Kamal et al [22] , Jose M et al [23] , Jose D et al [24] and Manda et al [25] from Southern India and study by Velhal et al [26] from Western India reported the incidence of AEFI as 57 %, 50.4 %, 54.3 %, 49.9 % and 94.4 % respectively, much higher than our finding. However, Joshi et al [27] from Northern India and Basavaraja et al [28] from Southern India reported the incidence of AEFI as 6.4 % and 4.3 % respectively after 1st dose of COVISHIELD, much lower than our figure.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the same indicators (including author, year of publication, number of participants, and vaccination efficacy and safety) could be extracted from eight qualitative analysis articles (62)(63)(64)(65)(66)(67)(68)(69), which are shown in Appendix 6. However, these studies could not be included in the meta-analysis due to insufficient data and/or descriptive explanations of vaccination efficacy and safety without the use of a parallel control, among other reasons.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…However, these studies could not be included in the meta-analysis due to insufficient data and/or descriptive explanations of vaccination efficacy and safety without the use of a parallel control, among other reasons. One article reported the VE (63), three articles reported antibody titer levels after vaccination (64,65,69), and six articles reported the occurrence of vaccine-related adverse events in the elderly (62,(64)(65)(66)(67)(68).…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…The most common symptoms found in a study in the tertiary hospital of Kerala were fever, local pain at the injection site, tiredness, chills, myalgia, headache, injection site stiffness, joint pain, and nausea/vomiting after the first dose. [ 23 ] National AEFI Committee of India, on June 4, 2021, reported the first death due to anaphylaxis to vaccine product of Covishield. [ 24 ] In phase II HCT of COVAXIN (6 μg with aluminum gels (Algel)-imidazoquinoline derivative (IMDG)), AEFI (expressed in percentage of total participants in 6 μg with Algel-IMDG group) for the first and second dose, respectively, were pain at the injection site, redness at the injection site, itching, stiffness in the upper arm, weakness in injection arm, body ache, fever, headache, malaise, weakness, rashes.…”
Section: Introductionmentioning
confidence: 99%